2017
DOI: 10.1515/tjj-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inner Nozzle Lip Thickness on Co-flow Jet Characteristics

Abstract: This paper presents the experimental results of subsonic and underexpanded sonic jets delivered from a central nozzle surrounded by a co-flow. The role of central nozzle lip thickness on the co-flow jet characteristics has been studied. The jet-mixing enhancement is achieved in the case of jet from the thick-lip nozzle compared to that of thin-lip nozzle. The extent of supersonic zone for the thick-lip is much shorter than the thin-lip jet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…They found that the increase in primary nozzle lip thickness reduces the potential core length of the primary jet. The effect of lip thickness (with a value of 15 mm) on co-flowing jets (flowing through a co-flowing nozzle) was also investigated by Srinivasarao et al, 18 which has a similar finding. To analyze the co-flowing jets characteristics with varying lip thickness, and to study the characteristics such as static pressure behavior, Mach number variation, and near-field turbulence, co-flowing jets with lip thickness of 2 mm, 10 mm, and 15 mm were studied by Naren et al 19 They reported that co-flowing jets with finite lip thickness (such as 10 mm and 15 mm) are effective mixing promoters than co-flowing jets with lip thickness of 2 mm.…”
Section: Introductionmentioning
confidence: 83%
“…They found that the increase in primary nozzle lip thickness reduces the potential core length of the primary jet. The effect of lip thickness (with a value of 15 mm) on co-flowing jets (flowing through a co-flowing nozzle) was also investigated by Srinivasarao et al, 18 which has a similar finding. To analyze the co-flowing jets characteristics with varying lip thickness, and to study the characteristics such as static pressure behavior, Mach number variation, and near-field turbulence, co-flowing jets with lip thickness of 2 mm, 10 mm, and 15 mm were studied by Naren et al 19 They reported that co-flowing jets with finite lip thickness (such as 10 mm and 15 mm) are effective mixing promoters than co-flowing jets with lip thickness of 2 mm.…”
Section: Introductionmentioning
confidence: 83%
“…Comparing to the single free jet, the core in the thin lip reduced to 45% and the thick lip core reduced to 58%. Similar work was conducted by Srinivasarao et al (2017) using a primary nozzle and secondary duct with lip thickness 3 mm (thin lip) and 15 mm (thick lip). The PCL decreased from 6 D p to 4 D p when the lip increases from 3 mm to 15 mm.…”
Section: Introductionmentioning
confidence: 89%
“…Hasil penelitian tersebut menunjukkan bahwa lip thickness pada turncated nozzle terpancung sudut dalam dapat meningkatkan kestabilan api difusi. Srinivasarao [10] juga meniliti pengaruh lip thickness pada nozzle dengan model combuster concentric jet flow namun dengan geometri nozzle dan burner yang berbeda. Penelitian tersebut hanya terfokus pada hasil eksperimen dengan kecepatan fluida sonic jet dan subsonik.…”
Section: Pendahuluanunclassified